Dekonstruksi Peran Diplomasi Perempuan Dalam Teks Pidato Menteri Luar Negeri RI Retno Marsudi - Supriatin, Adhe Riatin; Napitupulu, Frengki (Jurnal Pustaka Komunikasi, 2025)
This study aims to deconstruct the meaning of women’s diplomacy in the speech delivered by Indonesia’s Foreign Minister Retno Marsudi at the 2024 Gagas RI Forum entitled “Women and Indonesia’s Diplomacy on the Global Stage.” The research adopts a critical qualitative approach using Jacques Derrida’s theory and method of deconstruction. The unit of analysis is the official transcript of the speech, analyzed through Peter Barry’s three levels of deconstructive reading: verbal, textual, and linguistic. The results reveal numerous gaps, contradictions, and fractures within the text that destabilize the idealized narrative of female diplomacy. The presence of Kartini as a metaphor, while intended to symbolize women’s empowerment, instead exposes ambiguities between female agency and submission under patriarchal structures. These findings suggest that the diplomatic text embodies ideological tensions and fragmented meanings that diverge from the speaker’s intentions. This study contributes to the fields of political communication, diplomacy studies, and critical discourse analysis by offering new interpretations of women’s representation in public and diplomatic discourse.